Astragaloside IV Downregulates β-Catenin in Rat Keratinocytes to Counter LiCl-Induced Inhibition of Proliferation and Migration. (28th May 2012) - Li, Fu-Lun; Li, Xin; Wang, Yi-Fei; Xiao, Xiu-Li; Xu, Rong; Chen, Jie; Fan, Bin; Xu, Wen-bin; Geng, Lin; Li, Bin
Abstract : Re-epithelialization is a crucial step towards wound healing. The traditional Chinese medicine, Astragalus membranaceus (Fisch) Bge, has been used for hundreds of years for many kinds of ulcerated wounds. Recent research has identified the active compound in this drug as astragaloside IV (AS-IV), but the underlying molecular mechanisms of its therapeutic action on keratinocytes remain poorly understood. In this study, we used an in vitro model of ulcer-like wound processes, lithium chloride (LiCl)-induced cultured mouse keratinocytes, to investigate the effects of AS-IV treatment. The effects on cell proliferation were evaluated by the MTS/PMS colorimetric assay, effects on cell migration were determined by a wound-healing scratch experiment, effects on the cell cycle were analyzed by flow cytometry, and effects on protein expression were analyzed by immunoblotting and immunofluorescence. LiCl strongly inhibited cell proliferation and migration, up-regulated β -catenin expression, and down-regulated proliferating cell nuclear antigen (PCNA) expression. AS-IV treatment attenuat the inhibition of proliferation and migration, significantly reducing the enhanced β -catenin expression, and recovering PCNA and β -tubulin expression. Thus, AS-IV mediates mouse keratinocyte proliferation and migration via regulation of the Wnt signaling pathway. Down-regulating β -catenin to increase keratinocyte migration and proliferation is one mechanism by which AS-IV can promote ulcerated wound healing.